Synthetic Biomaterials in Vital Pulp Therapy: A Narrative Review of Conventional and Emerging Approaches - Turbatmath, Ketaki; Antony S, Delphine Priscilla (Journal of Neonatal Surgery, 2025)
Preservation of pulp vitality is a cornerstone of conservative dentistry and endodontics. The success of vital pulp therapy (VPT) depends heavily on the biomaterials employed, which must provide antimicrobial protection, biocompatibility, sealing ability, and stimulation of reparative dentinogenesis. Calcium hydroxide was historically regarded as the gold standard, but its high solubility, poor sealing, and porous dentin bridge formation limit its long-term success. Mineral trioxide aggregate (MTA) revolutionized VPT by offering superior sealing and bioactivity, though its high cost, difficult handling, and risk of tooth discoloration restrict widespread use. Newer calcium silicate-based materials such as Biodentine and TheraCal LC were developed to overcome these drawbacks, combining improved handling with bioactive potential. In parallel, emerging synthetic biomaterials such as bioactive glasses, enamel matrix derivatives, and dentin matrix hydrogels have demonstrated the ability to stimulate true pulp regeneration through biomimetic mechanisms. This narrative review consolidates current evidence on conventional and emerging synthetic biomaterials in VPT. Comparative insights highlight their strengths, limitations, and translational challenges. While synthetic agents have advanced clinical outcomes, further innovation and validation are required to achieve predictable pulp preservation and regeneration